Autoclaved rice: The textural property and its relation to starch leaching and the molecular structure of leached starch. (15th June 2019) - Li, Hongyan; Yu, Lu; Yu, Wenwen; Li, Haiteng; Gilbert, Robert
Highlights: Sensory properties of cooked rice are important for consumer acceptance. Autoclaving mainly affects stickiness of cooked rice, not hardness. Sensory properties controlled by molecular structure of leached starch. Molecular structure of leached starch is slightly affected by the cooking method. Stickier texture of autoclaved rice from more amylopectin leaching during cooking. Abstract: Autoclave cooking is used to produce "convenience" rice. In this study, autoclaving effects on sensory properties are investigated, and mechanistic explanations in terms of the underlying molecular structure are explored by analyzing this structure by size-exclusion chromatography and fitting the results with models based on biosynthetic processes. Compared to steam cooking, autoclaving produces stickier texture, and slightly affects hardness. It is found that molecular sizes of leached starch of both autoclaved and steam cooked rice are similar, but significantly smaller than that of the parent grain starch; model fitting parameters of leached amylopectin and amylose structures between autoclaved rice and steam cooked rice display no large variations. The amount of leached amylopectin (an important texture-controlling parameter) of autoclaved rice is higher than that of steam cooked rice. Correlation analysis indicates that, compared to steam-cooked rice, the stickier texture of autoclaved rice is caused by more amylopectin leaching during autoclaving.